Metabolic changes induced by pre-administration of L-alanyl-glutamine and Omega-3 in Wistar rats subjected to sepsis - Sena,José Ivamberg Nobre de (2010)
PURPOSE: To evaluate the metabolic changes induced by pre-administration of L-alanyl-glutamine (L-Ala-Gln) and omega-3 (ω-3) in rats subjected to sepsis. METHODS: Eighteen male Wistar rats were randomized into three groups (n=6) and treated with saline (group Control-G-1), L-Ala-Gln (0.75 mg /kg , G-2) or ω-3 (0.2 g /kg, G-3 ) administered intravenously 3, 2 and 1 day and 30 minutes before induction of sepsis. Samples (blood, striated muscle and liver) were collected 48 hours after induction of sepsis, to measure the concentrations of metabolites (pyruvate, lactate, glucose and ketone bodies. RESULTS: There was a significant increase in muscle glycolysis and gluconeogenesis in the liver in rats treated with L-Ala-Gln and ω-3, compared to the control group, 48 hours after induction of sepsis. CONCLUSION: Pre-administration of L-Ala-Gln or ω-3 to rats subjected to sepsis resulted in similar metabolic changes, by rising glycolysis in peripheral tissues and stimulating hepatic gluconeogenesis and ketogenesis, resulting in increased energy supply to septic rats.